Effect of increasing broiler slaughter weight on growth performance, economics, immunity and chemical composition of meat: Meat quality of broiler chicken - G.K. NAGRE; M.M. KADAM; D.B. BHAISARE; A.R. PATIL; Y.P. GADEKAR; K.S. RATHOD (Indian Journal of Poultry Science, 2025)
The objectives of this study were to determine the effects of slaughter weight on productive performance, economics, immune status and chemical composition of broiler meat at six different weights or age. For this purpose, a total of 280 straight run Vencobb-430 broiler chicks were used. The chicks were divided evenly into eight groups, with each group containing 35 chicks. Broilers were reared until different slaughter weights viz. 1.0-1.2, 1.5-1.7, 2.1-2.2, 2.5-2.7, 2.8-3.0 and 3.3-3.5 kg. Productive traits were recorded at different slaughter weights or ages. To study the effect of broilers slaughter weight on chemical composition and immune status, one bird from each group was slaughtered at each stage of approximately 1.0-1.2, 1.5-1.7, 2.1-2.2,2.5-2.7,2.8-3.0 and 3.3-3.5 kg live body weight. The findings indicated that the slaughter age had a positive impact on both ultimate body weight and body weight gain and significantly (P<0.001) different between all groups. Broiler live body weight was increased by about 66 % for the late slaughter age group. HI response of broiler birds significantly (P<0.01) increased from 0.38 at 24 days, 2.16 at 28 days, 2.27 at 34 days, 2.70 at 39 days to 3.18 at 42 days and 3.25 in at 48 days of slaughter. Moisture % and nitrogen free extract (NFE) % in chicken meat, was significantly (P<0.05) decreased from 71.18 % to 67.88 % and 79.44 to 70.24 %when slaughter age increased upto 48th days of age whereas, crude protein (CP) and ether extract (EE) % were significantly increased from 1.0-1.2 kg at 24 days to 3.3-3.5 kg slaughter weight at 48 days of age. However, ash % was not significantly (P>0.05) affected in the entire study period. Considering the outcomes of this investigation, it was concluded that delaying slaughter age produced increased weight, increased DM (Dry Matter), CP and EE % and deprived immune status of broiler birds.